Metabolic and Hormonal Determinants of Glomerular Filtration Rate and Renal Hemodynamics in Severely Obese Individuals - Edoardo Vitolo; Eleonora Santini; Antonio Salvati; Duccio Volterrani; Valerio Duce; Rosa Maria Bruno; Anna Solini (Obesity Facts, 2016)
Objective: Renal function is often compromised in severe obesity. A true measurement of glomerular filtration rate (GFR) is unusual, and how estimation formulae (EstForm) perform in such individuals is unclear. We characterized renal function and hemodynamics in severely obese individuals, assessing the reliability of EstForm. Methods: We measured GFR (mGFR) by iohexol plasma clearance, renal plasma flow (RPF) by 123I-ortho-iodo-hippurate, basal and stimulated vascular renal indices, endothelium-dependent and -independent vasodilation using flow-mediated dilation (FMD) as well as metabolic and hormonal profile in morbid, otherwise healthy, obese subjects. Results: Compared with mGFR, the better performing EstForm was CKD-EPI (5.3 ml/min/1.73 m2 bias by Bland-Altman analysis). mGFR was directly related with RPF, total and incremental glucose AUC, and inversely with PTH and h8 cortisol. Patients with mGFR below the median shown significantly higher PTH and lower vitamin D3. Basal or dynamic renal resistive index, FMD, pulse wave velocity were not related with mGFR. In an adjusted regression model, renal diameter and plasma flow remained related with mGFR (R2 = 0.67), accounting for 15% and 21% of mGFR variance, respectively. Conclusions: CKD-EPI formula should be preferred in morbid obesity; glucose increments during oral glucose tolerance test correlate with hyperfiltration; RPF and diameter are independent determinants of mGFR; slightly high PTH values, frequent in obesity, might influence mGFR.